Keloid Scars Arising after Follicular Unit Extraction Hair Transplantation - Alhamzawi, Nabeel K. (J Cutan Aesthet Surg, 2020)
Hair transplantation is considered safe compared to other cosmetic procedures. However, scarring is still an inevitable potential complication. Keloid scarring is a rare complication of hair transplantation and usually associated with strip harvesting rather than follicular unit extraction (FUE). A case of keloids at the donor site following FUE hair transplantation is presented. Hair transplant practitioners should be aware of the risks of the procedure when considering hair restoration to ensure safer outcomes.